Influence of Brand Awareness, Brand Trust, and E-Wom on Purchase Decisions on Tokopedia E-Commerce Users in Singaraja - Kadek Deni Darmayani; Trianasari, Trianasari; Suarmanayasa, I Nengah (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effects of brand awareness, brand trust, and electronic word of mouth (e-WOM) on purchase decisions among Tokopedia users in Singaraja. Using a quantitative approach, data were collected through questionnaires from 96 respondents and analyzed using validity, reliability, multiple linear regression, t-test, F-test, and coefficient of determination. The results show that brand awareness, brand trust, and e-WOM each have a positive and significant effect on purchase decisions, both partially and simultaneously. The model explains 30.6% of purchase decisions. These findings imply that Tokopedia should strengthen brand recognition, consumer trust, and positive online reviews to improve purchasing decisions. Keywords: Brand Awareness; Brand Trust; E-WOM; Purchase Decision; Tokopedia; Consumer Behavior.